2.3 Ghz Lte Antenna Design Using Triangle Geometry and Array Structure - Septima, Uzma; Yulindon; Setiawan, Herry; Nasrul; Putra (Brilliance: Research of Artificial Intelligence, 2023)
Microstrip antenna is one of the most important devices in telecommunications systems. One example is the design of a microstrip antenna on a long time evolution (LTE) device. Disadvantages of this microstrip antenna include low gain, poor directionality, low efficiency, resistance losses on the feed line and narrow bandwidth. This research will design a triangular patch array microstrip antenna to increase the gain so that it can meet the desired work specifications with a working frequency of 2.300MHz. The antenna is designed using FR-4 Epoxy substrate material with a size of 120 mm x 60 mm, which has a dielectric constant (?r) of 4.3, a loss tangent of 0.035 and a material thickness of 1.6 mm. Antenna designed using CST studio suite software 2018. The results obtained in the working frequency band 2280.4 MHz – 2370.0 Mhz, middle frequency 2332 MHz, return loss – 47.360dB, bandwidth 24.7MHz, VSWR 1.008, gain 4.39dBi, impedance 49.90 , and unidirectional radiation pattern.